Digital Transformation and Sustainable Performance in the Green Economy Era: The Mediating Role of Data-Driven Management - Luwiha Luwiha; Desi Derina Yusda; Fakhrur Rozi (LPPM STIAB Jinarakkhita Lampung, 2026)
This study examines the effect of digital transformation on sustainable performance through the mediating role of data-driven management in the Green Economy era. Digital transformation is conceptualized through business process digitalization, digital system integration, automation, and the utilization of data analytics, while sustainable performance is reflected in its economic, environmental, and social dimensions. This study adopts a quantitative explanatory approach using survey data collected from organizational members involved in digital technology utilization and data-based decision-making processes. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings reveal that digital transformation positively influences data-driven management and sustainable performance. In addition, data-driven management has a positive effect on sustainable performance and serves as a significant mediator in the relationship between digital transformation and sustainable performance. These results indicate that organizations can strengthen sustainable performance by accelerating digital transformation initiatives while enhancing data-driven decision-making capabilities. This study contributes to the growing literature on digital transformation and sustainability by providing empirical evidence of the mediating role of data-driven management in achieving sustainable performance within the context of the Green Economy.